2021
DOI: 10.1111/jdi.13700
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical detection of enteroviruses in pancreatic tissues of patients with type 1 diabetes using a polyclonal antibody against 2A protease of Coxsackievirus

Abstract: Aims/Introduction: The need for antiserum for immunohistochemical (IHC) detection of enterovirus (EV) in formaldehyde-fixed and paraffin-embedded samples is increasing. The gold standard monoclonal antibody (clone 5D8/1) against EV-envelope protein (VP1) was proven to cross-react with other proteins. Another candidate marker of EV proteins is 2A protease (2A pro ), which is encoded by the EV gene and translated by the host cells during EV replication, and participates processing proproteins to viral capsid pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…As another positive control for VP1 antisera (5D8/1) by IHC, formalin-fixed and paraffin-embedded pancreas from FT1DM, which was ascertained by in situ hybridization 41 , was stained for VP1 (5D8/1) and was positive for enterovirus. New antisera against EV-2A pro (ET2112) were raised, and it was confirmed that the antiserum stained CVB1 in virus-infected Vero cells and also stained VP1-positive islet cells of FT1DM 40 , 41 . In this study, this antiserum was absorbed with 2A pro peptide of CVB1 at 10 ng/ml in SPIDDM (Supplemental Fig.…”
Section: Methodsmentioning
confidence: 88%
See 4 more Smart Citations
“…As another positive control for VP1 antisera (5D8/1) by IHC, formalin-fixed and paraffin-embedded pancreas from FT1DM, which was ascertained by in situ hybridization 41 , was stained for VP1 (5D8/1) and was positive for enterovirus. New antisera against EV-2A pro (ET2112) were raised, and it was confirmed that the antiserum stained CVB1 in virus-infected Vero cells and also stained VP1-positive islet cells of FT1DM 40 , 41 . In this study, this antiserum was absorbed with 2A pro peptide of CVB1 at 10 ng/ml in SPIDDM (Supplemental Fig.…”
Section: Methodsmentioning
confidence: 88%
“…The 5D8/1 and 6E9-2 antibodies when incubated overnight with VP1 protein showed complete abolition of immunostaining for VP1 (Supplemental Fig. S 8a–h) 39 , 40 . Ten consecutive pancreatic sections in each case from 12 SPIDDM pancreases were stained for VP1 using 5D8/1 and 6E9-2.…”
Section: Methodsmentioning
confidence: 98%
See 3 more Smart Citations